Glocalization: An Emerging Approach in Teacher Education - Radjuni, Abubakar J. (Open Access Indonesia Journal of Social Sciences, 2021)
Due to the increasingly complex and rapidly changing world, teachers’ role has continuously been changing and they have to open their eyes to the reality of the world. Particularly in Sulu, pedagogical and technological development in education are remained outdated and traditional. Yet, changes in the past 20 years for the environment, employment, relationships, health and wealth, in society, safety, culture, communication, and even the values demonstrated by society’s leaders. We could argue that virtually everything has changed and that students today think, act and understand things differently from how their parents did. The same with the changes happens in educational context today which the teachers need to “think globally and act locally”. This papers anchored on the view that glocalization in education is the effective approach for the nation to catch up with the trends at par with other developed nations. It is presumed the education today has changed so much, it is appropriate that we look at what teachers need to do in order to prepare young people for the modern world, with its increasingly complex and rapidly changing future. This is the effective approach to make our educational environment in Sulu more relevant to the society. Therefore, the teachers must be updated and research-oriented which help our government toward promoting quality education in Sulu and the country as a whole. This paper is solely based on the secondary data. The different sources of data are journal articles, websites, books, reports of various organizations, articles published in international and national papers, etc. This paper gives a brief description of the glocalization in education as an approach to education. Hence, the main objective of this paper is to highlight the glocalization in education as an approach toward achieving quality education which covers changing nature of education, glocal teacher and glocal teachers’ edge.